If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-6m+6-4=2
We move all terms to the left:
6-6m+6-4-(2)=0
We add all the numbers together, and all the variables
-6m+6=0
We move all terms containing m to the left, all other terms to the right
-6m=-6
m=-6/-6
m=1
| 5(n+2)=-17-4n | | 2b-3=0.3 | | 5.6x+900=31.36+30x | | 4x+30=8x-6 | | 1/3(6/7-2x)-3/7=6/7 | | 60=4^2x | | 15x+1=18x-15 | | 5x+1=18x-15 | | 90x-500=40x+500 | | X-8x+11=-10 | | 5x-2-x=9x+3x+10 | | 32x+3=4⋅2x | | -1.2x+2.5=0.8x+6.5 | | 5(n+2)=-7-4n | | 3n-13=23 | | 1.2=2.4+-3b | | 7(x9)=4(x-8) | | 293=188-v | | 2x+30=(2/3)*6x | | 23=239-y | | (3/2)^x=9/2 | | 8w+56=164 | | 6x^2+12x-36=-27 | | -y-196=95 | | 182=77-w | | 24x+12=8x2x | | 158-v=64 | | 6(4x+2)=8x2x | | 75+35+x=180 | | (-7.4+n=9.11 | | −(2/5)+(2/3)w=−(3/2) | | s-10=20.99 |